Anthelmintic Trials Against Gastrointestinal Nematodes and Lungworms in Sheep - Jameil Alani, Abdul Aziz (Al-Mukhtar Journal of Sciences, 2007)
The Efficacy of some anthelmintics against various gastrointestinal nematodes and lungworm naturally infected sheep were studied. .Efficacy was determined by following the total egg count using McMaster technique, Sheep were infected with Ostertagia spp, Chabertia ovina, Marshallagia marshalli and Moniezia expansa. Lungworms were Dictyucdus filaria , Muellerius capillaris and Protrongylus spp. Efficacy were 90%,88.63%, 97.62% and 100% for Levamisole , Ivomic , Albendazole and Tetramisole respectively. Efficacy of Tetamisole was 100% aginst M.capillaris and D.filara.In addition that the lungworms were not affected by Levomisole.